NEBio’s Opinion: “Feeding on Advanced Dementia” - H. Carneiro, António; Carneiro, Rui; Freire, Elga (Portuguese Journal Internal Medicine, 2021)
The NEBio (Center for Bioethics Studies) of SPMI appreciated the text of the Consensus Feeding in Dementia at request of the authors. An opinion was prepared based on applicable ethical, moral, deontological and legal standards. NEBio concludes by the ethical adequacy of the proposals and of the submitted text and considered it an important contribution to clinical practice in end-of-life situations.